Changes in Inward Rectifier K+ Channels in Hepatic Stellate Cells During Primary Culture - Lee, Dong Hyeon; Kong, In Deok; Lee, Joong-Woo; Park, Kyu-Sang (Yonsei medical journal, 2008)
This study examined the expression and function of inward rectifier K(+) channels in cultured rat hepatic stellate cells (HSC). The expression of inward rectifier K(+) channels was measured using real-time RT-PCR, and electrophysiological properties were determined using the gramicidin-perforated patch-clamp technique. The dominant inward rectifier K(+) channel subtypes were K(ir)2.1 and K(ir)6.1. These dominant K(+) channel subtypes decreased significantly during the primary culture throughout activation process. HSC can be classified into two subgroups: one with an inward-rectifying K(+) current (type 1) and the other without (type 2). The inward current was blocked by Ba(2+) (100 microM) and enhanced by high K(+) (140 mM), more prominently in type 1 HSC. There was a correlation between the amplitude of the Ba(2+)-sensitive current and the membrane potential. In addition, Ba(2+) (300 microM) depolarized the membrane potential. After the culture period, the amplitude of the inward current decreased and the membrane potential became depolarized. HSC express inward rectifier K(+) channels, which physiologically regulate membrane potential and decrease during the activation process. These results will potentially help determine properties of the inward rectifier K(+) channels in HSC as well as their roles in the activation process.